An analysis of the Visual communication by the city of Cape Town about the water crisis - Landman, Matthew (The IIE, 2018)
The aim of this particular study was to analyse the way in which the City of Cape Town (CoCT) communicated the water crisis visually. This could have been done through the use of either traditional or modern media channels. Traditional media are various media channels that were more prominent in the past, therefore traditional methods are usually associated with targeting the older generations as they would be more familiar with it. Traditional media usually has a high reach and frequency that can target a broad market, which in some cases can be the goal of a brand or company. However impact is usually what brands want to achieve. To achieve impact, brands usually have to have a good understanding of their target market so that they understand their needs and desires. Modern media exists within a digital space and is linked to the internet such as social media and websites. The methodology that has been incorporated for this study is interpretivism. This approach takes human interest and diversity into account as people perceive visuals and consume media differently. The findings of the study showed that there is necessity for both visual narrative and universally interpreted visuals. This was due to the multi-cultural and diverse speaking individuals that the water crisis aimed towards. In addition to what has been said, participants wanted to use trustworthy source material with regards to the media that they consumed, therefore trusted infographics and various forms of Visual Communication that was done by the CoCT. The main limitation to the study was trying to understand exactly what the participants were trying to say. Due to it being a qualitative study, the researcher had to try keep all questions relatively open-ended and opinion based.
Keywords: Water crisis; Visual communication; Brand communication; Digital communication